The Fault In Our Stars By John Green - Agustia Anusi; Feby Meuthia Yusuf (Jurnal Ilmiah Langue and Parole, 2017)
The problem in this thesis is the irony of love story between two human beings who are in love, the irony occurs when the fate has separated their love story. The tragic story of Hazel and Augustus' love is inspired by the author's visit to chronic cancer patients at the hospital, about their hopes and love that would be impossible to achieve. In this writing, library research is taken as the method of data collection. As for data analysis method, the writer performs systematic procedures by understanding the novels, the characters of Hazel and Augustus, as well as the structural theory. Data collection technique uses documentation technique in finding relevant data to the subject of analysis. In data analysis techniques, the writer uses structural technique by analyzing the novel based on the elements that shape them. The results of research in this thesis are: 1) destiny seems to separate the love story of Hazel and Augustus, where Hazel is suffered from the chronic cancer while Augustus is in good shape, but Augustus is willing to love Hazel until the end of life, 2) destiny continues to play their love story, this time it is August that suffers from chronic illness and is on the verge of death, while Hazel's condition is getting better. This time, it is Hazel that loves Augustus until the end of his life, and faithfully accompanied him; 3) the irony has occurred in the love story of Hazel and Augustus where the unfair destiny has turned the deaths and hopes on both of them, the one who is almost dies has become better, on the contrary the one who is healthy has been picked by the death in the end. The love story and hope of being together have been ironically played by the fate.